Mineral besisebagai pengikat vitalisas ikan kerapu bebek (Cromileptes altivelis) saat kondisi stres hipoka - Mia Setiawati; TI Winarno; MA Suprayudi; I Mokoginta; W Manalu (Jurnal Ilmu Pertanian Indonesia, 2007)
Humpback grouper (Cromileptes altivelis) is sensitive to stress that coused low growth rate, mortality, and harvest. Iron is micronutrient that can enhance the immunity. This experiment was conducted to determine the iron supplement in the feed for humpback grouper fish to vitality increase at hypoxia stress condition. The fish weight 4.14+-0.01 g/ind. and was cultured in 60x40x50 cm aquarium and stocked at a density of 10 ind./aquarium. After reader for 61 days, the fish was